The Efficacy of Acupuncture on Tic Disorders in Children: A Retrospective and Propensity Score-Matched Study - Hai-Zhen You (Frontiers Media S.A., 2021)
Background : Acupuncture has been considered as a complementary or alternative therapy for children with tic disorders (TD), but its efficacy remains largely unknown. This study retrospectively examined the efficacy of acupuncture treatment for TD in children over the course of 12 weeks.Methods: Data were collected from Traditional Chinese Medicine clinics in a public pediatric hospital in Shanghai between June 2020 and March 2021. A total of 250 patients with TD were included in the study, with 122 patients exposed to acupuncture therapy combined with conventional treatment (observation group), and 128 patients exposed to conventional treatment alone (control group). Propensity score matching analyses were used to balance baseline characteristics, resulting in 78 matched patients for each group. Reductions in the Yale Global Tic Severity Scale (YGTSS) total score were analyzed in the two groups after 12 weeks of treatment.Results: The two groups reached equilibrium in terms of baseline demographic characteristics and YGTSS total score after the propensity score matching (P > 0.05). Compared to the control group, the reduction in the YGTSS total score after 12 weeks of treatment was greater for the observation group (OR = 2.94, 95% CI: 1.03, 8.39, P = 0.04), and this association was stronger for patients who had significant vocal tics (β = 0.29, 95% CI: 0.88, 2.68, P = 0.001). The clinical efficacy for the observation group was significantly better than the control group.Conclusions: We provided preliminary evidence supporting the therapeutic effect of acupuncture for TD in children. Hence, our findings indicate that acupuncture could be an adjuvant treatment efficacious for TD in children, especially for vocal tics.